A forcing collision resolution approach able to prioritize traffic in CSMA-based networks - Ricardo Moraes (2010)
In this paper, a new Traffic Separation mechanism (TSm) is proposed for CSMA-based networks. The TSm mechanism is intended to be used as an underlying traffic separation mechanism, able to prioritize traffic in CSMA-based networks. It allows the coexistence of standard CSMA (non-modified) stations with TSm (modified) stations in the same communication domain. When a station implementing the TSm mechanism has a high-priority message to transfer, it will impose its transfer prior to any message from standard CSMA stations. This behavior guarantees the highest transmitting probability to the TSm-enabled station in open communication environments. Therefore, the TSm approach can be used as an underlying mechanism to build real-time communication systems upon CSMA-based networks. The behavior of the TSm mechanism was assessed by simulation in the case of a relevant CSMA-based network (IEEE 802.11). The simulation analysis shows that the TSm mechanism guarantees values for both the throughput and the average access delay that significantly improve the results obtained for standard IEEE 802.11 stations.